Report on fractures of trilayered all-ceramic fixed dental prostheses. (October 2016) - Belli, Renan; Scherrer, Susanne S.; Lohbauer, Ulrich
Highlights: Fractography is used to evaluate 3 fracture cases of trilayered all-ceramic dental prostheses. Photographs and SEM images are used to track fracture markings and find the causes of fracture. In all three cases fracture initiated, or were triggered by pre-existing cracks in the zirconia framework. Abstract: Three cases of trilayered fixed dental prostheses fractured in vivo are fractographically analyzed to identify causes of failure. In all cases fractures initiated from a preexistent crack/defect in the zirconia framework produced previous to the fusion firing of a lithium disilicate veneering ceramic. In two cases zirconia framework pre-cracks were found to have been infiltrated with the intermediate fusion glass that diffused therein during sintering. This report highlights the susceptibility of zirconia to grinding damage and its role in limiting the lifetime of zirconia-based fixed dental prostheses.